Fetal umbilical cord cyst may evolve to omphalocele during pregnancy. Issue 3 (14th November 2019) - Suzuki, Toshifumi; Yamamoto, Yuka; Nakamura, Hiroki; Sei‐Okawa, Kiguna; Maruyama, Yojiro; Takeda, Jun; Makino, Shintaro; Yamataka, Atsuyuki; Itakura, Atsuo
Abstract: Omphalocele is rarely complicated by umbilical cord cysts. In our case, an umbilical cord cyst and fetal ascites were detected at 26 weeks' gestation in a fetus with trisomy 13. This changed to omphalocele with subsequently absorbed fetal ascites at 35 weeks' gestation. We propose two hypotheses. The abdominal wall may have been physically pierced or an omphalocele might have preexisted, and the intestinal tract in the hernia sac was pushed by fetal ascites.